Relating Systems Thinking & Design 2013. Emerging Contexts for Systemic Design - Sevaldson, Birger (FormAkademisk, 2013)
AHO – Oslo School of Architecture & Design, Norway, invites to the Relating Systems Thinking and Design to a free and open symposium over two days 9th-11th October 2013, with a preceding full day with diverse workshops and a subsequent special issue in FORMakademisk.